2021
DOI: 10.1186/s12014-020-09304-8
|View full text |Cite
|
Sign up to set email alerts
|

Label-free proteomic analysis of serum exosomes from paroxysmal atrial fibrillation patients

Abstract: Background Atrial fibrillation (AF) is the most common cardiac heterogeneous rhythm disorder. It represents a major cause of mortality and morbidity, mainly related to embolic events and heart failure. Mechanisms of AF are complex and remain incompletely understood. Recent evidence suggests exosomes are membrane-coated objects released by many cell-types. Their presence in body fluids and the variable surface composition and content render them attractive as a mechanism for potential biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Cellular protein synthesis consists of three distinct stages, initiation, elongation, and termination, and all stages depend on translation factors. 30 Herein, we speculate that ribosomal proteins in pigeon milk might be from the exfoliated crop epithelium and mainly participated in the synthesis of other pigeon milk proteins with biological functions. In addition to ribosomes, we also found the keratin, peroxiredoxin, annexin, and heat shock proteins were the main pigeon milk proteins.…”
Section: ■ Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cellular protein synthesis consists of three distinct stages, initiation, elongation, and termination, and all stages depend on translation factors. 30 Herein, we speculate that ribosomal proteins in pigeon milk might be from the exfoliated crop epithelium and mainly participated in the synthesis of other pigeon milk proteins with biological functions. In addition to ribosomes, we also found the keratin, peroxiredoxin, annexin, and heat shock proteins were the main pigeon milk proteins.…”
Section: ■ Discussionmentioning
confidence: 92%
“…In addition, our results indicated that eukaryotic translation initiation factor 2 and tRNA synthetase have a high degree of connectivity of ribosome. Cellular protein synthesis consists of three distinct stages, initiation, elongation, and termination, and all stages depend on translation factors . Herein, we speculate that ribosomal proteins in pigeon milk might be from the exfoliated crop epithelium and mainly participated in the synthesis of other pigeon milk proteins with biological functions.…”
Section: Discussionmentioning
confidence: 94%
“…Ni et al conducted a proteomic analysis of serum EVs comparing paroxysmal AF patients with healthy subjects. These two groups were proven to have different expression levels of many proteins mainly involved in anticoagulation, complement system, and protein folding, as indicated by the bioinformatic analysis [ 60 ]. Zietzer et al proved that patients suffering from AF had higher levels of large EVs derived from platelets in the left atrial appendage than patients with no AF.…”
Section: Extracellular Vesicles In Patients With Atrial Fibrillationmentioning
confidence: 99%
“…These microbial communities may release EVs during the onset of myocardial injury, which, depending on their origin, could be enriched in MMP9 and elicit a protective role during plaque rupture [180]. Likewise, Ni et al characterized the protein profile of serum exosomes from atrial fibrillation patients and found 40 elevated proteins and 75 reduced proteins when compared to healthy controls [181]. Interestingly, these proteins were associated with anticoagulation, the complement system and protein folding.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%